STRUCTURAL AND OPTICAL CHARACTERIZATION OF HEAT-TREATED SIC PARTICLES DERIVED FROM RICE HUSK ASH FOR PHOTOVOLTAIC - Riza, Ramzul Irham; Ngafwan; Masyrukan; Krisnoadi, Ridwan; Kurniawan, Adhyaka Billy (Universitas Muhammadiyah Surakarta, 2026)
This study explores the potential of nanoscale silicon carbide (SiC) particles synthesized from rice husk ash to enhance light absorption characteristics in solar panel applications. The SiC particles were produced by burning rice husks, followed by purification and division into two groups: one group underwent heat treatment at 400 °C, while the other was kept untreated for comparative analysis. High-Energy Milling (HEM) for 60 hours was used to reduce the particle size of selected samples. Comprehensive characterization was performed using Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and UV-Vis spectroscopy in the wavelength range of 200–1100 nm. The results of the study indicate that heat-treated SiC exhibits significantly reduced agglomeration and better particle dispersion compared to untreated samples. FTIR analysis confirmed the presence of additional functional groups (C=C and O–H) in the treated SiC, which contribute to surface chemical modification. Most importantly, the UV-Vis spectra show that the treated SiC maintains consistently higher absorbance values (0.5–0.6) in the visible to near-infrared region (400–1100 nm), whereas the untreated SiC exhibits a decreasing trend (0.4–0.2). These findings suggest that thermal processing can enhance the optical performance of SiC nanoparticles by improving dispersion and introducing functional groups that strengthen light-matter interactions. The superior absorption characteristics of the processed SiC demonstrate promising potential as an additive or nanostructured layer to improve photon capture and overall efficiency in photovoltaic devices